2016
DOI: 10.1186/s12911-016-0377-1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive biases associated with medical decisions: a systematic review

Abstract: BackgroundCognitive biases and personality traits (aversion to risk or ambiguity) may lead to diagnostic inaccuracies and medical errors resulting in mismanagement or inadequate utilization of resources. We conducted a systematic review with four objectives: 1) to identify the most common cognitive biases, 2) to evaluate the influence of cognitive biases on diagnostic accuracy or management errors, 3) to determine their impact on patient outcomes, and 4) to identify literature gaps.MethodsWe searched MEDLINE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
614
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(629 citation statements)
references
References 68 publications
4
614
0
11
Order By: Relevance
“…1) to arrive at a final decision can be highly variable and lead to inter-physician variability and heterogeneity in decision-making [11]. While the degree of inter-physician variability for ET patient selection has not been studied, the existence of such variability is supported by Saposnik et al[11, 12] who found superior predictive accuracy and precision of the iSCORE over clinical judgement by stroke physicians.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…1) to arrive at a final decision can be highly variable and lead to inter-physician variability and heterogeneity in decision-making [11]. While the degree of inter-physician variability for ET patient selection has not been studied, the existence of such variability is supported by Saposnik et al[11, 12] who found superior predictive accuracy and precision of the iSCORE over clinical judgement by stroke physicians.…”
Section: Introductionmentioning
confidence: 61%
“…1) to arrive at a final decision can be highly variable and lead to inter-physician variability and heterogeneity in decision-making [11]. While the degree of inter-physician variability for ET patient selection has not been studied, the existence of such variability is supported by Saposnik et al[11, 12] who found superior predictive accuracy and precision of the iSCORE over clinical judgement by stroke physicians. Prognostic scores that combine clinical and/or radiographic variables that are available to the clinician prior to ET (pre-intervention scores) have been validated across a wide range of LVOS populations and appear to have moderate prognostic accuracy for good clinical outcome defined as modified Rankin Scale (mRS) score of 0–2 at 3 months.…”
Section: Introductionmentioning
confidence: 61%
“…From a psychological point of view, cognitive biases may affect clinical reasoning processes which may lead to errors in the diagnosis, management and treatment of medical conditions and can be associated with poorer outcomes such as medication non-compliance, overuse, patients’ dissatisfaction, medical complaints, increased length of stay, increased costs and ultimately unnecessary deaths 8. Several factors can increase the likelihood of cognitive biases such as person (eg, cognitive loading, fatigue), patient (eg, complex patient presentation, number of comorbidities) and system factors (eg, poorly accessible IT, poor teamwork/communication) 8–12…”
Section: Discussionmentioning
confidence: 99%
“…They fall into three categories as set out in table 1. Most of the factors listed were readily self-identified during our consultant interviews except for ‘cognitive biases and personality traits’ 25. However, reflective discussion was revealing and often resulted in clinicians’ surprise at his or her own biases.…”
Section: Avoiding Nbts: Obstacles In the Waymentioning
confidence: 99%